(untitled) (ACME, 2021)
The aim of this work is to provide a cartography of the notion of individuation, in its relations with the dimension of the pre-individual, working between Gilles Deleuze and Gilbert Simondon, through a path of “fraying” of the human. Ultimately, we would like to show how it is possible to re-semantize the vexata quaestio of the “End of Man”, re-reading it as a problem of borders and multiple layers, always active and in becoming. In order to highlight this constitutive interrelation between the field of the pre-personal and the processes of individuation, we will analyze the concepts of difference, affectivity and “ontological communism”.